2017
DOI: 10.1016/j.jcma.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications and extraintestinal manifestations of inflammatory bowel disease in Taiwan: A population-based study

Abstract: Our study found that CD had a more complicated course, with a higher incidence of GI complications and EIMs. However, the prevalence of intestinal complications, perianal disease, and major EIMs was less common than in Western countries. This study provided a distinct clinical feature of IBD in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…A recent analysis of IBD clinical presentation using data extracted from NHIRD found that 11.2% of UC cases in Taiwan from 1998 to 2011 exhibited gastrointestinal complications and extraintestinal manifestations 24. During the 14-year study period, the prevalence of extraintestinal manifestations increased from 2.8% to 26.6%.…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of IBD clinical presentation using data extracted from NHIRD found that 11.2% of UC cases in Taiwan from 1998 to 2011 exhibited gastrointestinal complications and extraintestinal manifestations 24. During the 14-year study period, the prevalence of extraintestinal manifestations increased from 2.8% to 26.6%.…”
Section: Resultsmentioning
confidence: 99%
“…In the ACCESS cohort, 19% of Asian IBD patients presented with EIMs . In Taiwan, EIMs were present among 11.9% of IBD patients; furthermore, the prevalence of EIMs increased from 2.3% in CD patients and 2.8% in UC patients to 25.9% and 26.6%, respectively, during a 14‐year follow‐up period …”
Section: Clinical Features Of Ibdmentioning
confidence: 99%
“…In western populations, joint manifestations (both peripheral and axial arthropathy) were the most common EIMs and affected 17–30% of IBD patients . Similarly, peripheral arthritis was the most common EIM in Taiwan and was present in 6.1% of IBD patients . Skin (5–15% vs. 0.3–1.8%) and ocular manifestations (3–6% to 0.1–0.3%) were more frequently reported in the West than in the East .…”
Section: Clinical Features Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of the immune interaction between enteric antigens and the enteral mucosa results in chronic, immune-mediated inflammation [3].…”
Section: Discussionmentioning
confidence: 99%